The safety evaluation of the atrial fibrillation radiofrequency catheter ablations with non-irrigated 4 mm tip catheters use - Doronin, A.; Suslina, J.; Riznyk, A.; Khanenova, V.; Marushko, Y.; Meshkova, M. (Ukrainian Journal of Cardiovascular Surgery, 2017)
The article analyzes own experience of catheter ablation to eliminate atrial fibrillation (AF) by conventional electrodes. We analyzed the complications of 500 consecutive procedures carried out in the period from 01.2013 till 12.2016, in the UCCC. Initial and repeat procedures were performed without navigation system. After 15–20 applications destructive electrode was removed and wiped. The average age of patients was 55,7±10,8 years. In patients with paroxysmal AF we produced 304 (60.8%) procedures, in perisitent – 196 (39.2%). Initial treatments conducted at 396 (79.2%) patients, 89 (17.8%) procedures performed repeatedly, in 13 (2.6%) – third time, and in 2 (0.4%) – the fourth. Fixed 8 (1.6%) significant complications: pericardial tamponade – 2 (0.4%), femoral artery aneurysm – 4 (0.8%), the atrio-venous fistula – 1 (0.2%), hematoma at the site of puncture – 1 (0.2%). Also recognized 5 (1.0%) cases of pericardial effusion, and 1 (0.2%) – transient atrioventricular block. Thus, the number of complications in the use of conventional electrodes is not higher than when using electrodes with a cooling function.